UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG SISWA DENGAN MENGGUNAKAN MEDIA DIGITAL BERBASIS WORDWALL PADA SISWA KELAS 1 DI SD NEGERI PADAASIH - Hermita Adela; Amalia, Arsyi Rizqia; Sutisnawati, Astri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the numeracy skills of first-grade students at SD Negeri Padaasih through the implementation of Wordwall-based digital media. The background of this research was the low numeracy skills of students, particularly in subtraction materials. The method employed was Classroom Action Research (CAR) conducted over two cycles, with each cycle consisting of two meetings. The research participants were 49 first-grade students, comprising 27 male students and 22 female students. Data were collected through observation and documentation, and then analyzed using quantitative descriptive techniques. The results showed that the implementation of Wordwall-based digital media had a positive impact on students’ numeracy skills. Student learning mastery in the pre-cycle phase was only 55% (23 students completed). After the intervention, student mastery increased to 65.5% (30 students completed) in Cycle I and reached 80.2% (41 students completed) in Cycle II, which successfully met the targeted success criteria of 80%. In addition, students’ learning motivation and participation during the teaching and learning process improved significantly. Therefore, the use of Wordwall-based digital media is effective in enhancing elementary school students’ numeracy skills.